Perspectives on Participation in Continuous Vocational Education Training–An Interview Study - Siegfried, Christin; Berger, Josephine (Frontiers in Psychology, 2020)
In European industrialised countries, a large number of companies in the healthcare, hotel and catering sector as well as in the technology sector are affected by demographic, political and technological developments resulting in a greater need of skilled workers with a simultaneous shortage of skilled workers (Codefop, 2015, 2016). Consequently, employers have to address workers who have not been taken into account such as low-skilled workers, workers returning from a career break, people with a migrant background, older people and jobseekers and train them, in order to guarantee the professionalization of this workforce (Festing & Harsch, 2018). CVET (Continuous Vocational Education and Training) is seen as an indispensable tool, since CVET has advantages for both employers and employees, it helps to increase the productivity of companies (Barrett & O’Connell, 2001), to prevent the widening of socioeconomic disparities (Dieckhoff, 2007) and to open up career opportunities for the workforce (Rubenson & Desjardins, 2009). However, participation rate on CVET seems to differ depending on institutional factors (such as sector and size of the company) and individual characteristics (such as qualification level, migration background, age and time of absence from work) (e.g. Rubenson & Desjardins, 2009; Wiseman & Parry, 2017). In contrast to previous research, our study aims to provide a holistic view of reasons for and against CVET, combining the different perspectives of employers and (potential) employees. The analysis of reasons and barriers was carried out based on semi-structured interviews. 57 employers, 73 employees and 42 jobseekers (potential employees) from the sectors retail, healthcare and social services, hotels and catering and technology were interviewed. Results point to considerable differences in the reasons and barriers mentioned by the disadvantaged groups. These differences are particularly significant between employees on the one side and employers as well as jobseekers on the other side, while the reasons to attend CVET of jobseekers are more similar to those of employers. The results can be used to tailor CVET more closely to the needs of (potential) employees and thus strengthen both the qualification and career opportunities of (potential) employees and the competitiveness and productivity of companies.